Localities and sites of Pulsatilla vernalis in the Julian Alps - Dakskobler, Igor; Sinjur, Iztok; Veber, Ivan; Zupan, Branko (Hacquetia, 2015)
Applying the standard Central-European method we phytosociologically studied the sites of Pulsatilla vernalis, a rare and protected species of Slovenian flora, in the frost hollows on mountain pastures Ovčarija and Za Grivo in the Fužina pasturelands (the Triglav mountains, the Julian Alps). We established that it grows in a unique community of swards and heaths which usually extends over small surfaces (4–10 m2) and is dominated by herbaceous perennial species (hemicryptophytes) and dwarf shrubs (chamaephytes) with mostly arcticalpine and south-European montane distribution. This community is explicitly (floristically and ecologically) different from the communities of swards and heaths described in the Julian Alps so far, so we classified it into a new association Pulsatillo vernalis-Dryadetum octopetalae ass. nova (order Rhododendro hirsuti-Ericetalia carneae) and subdivided it into two, floristically and ecologically clearly distinguished subassociations -ericetosum carneae subass. nova and -vaccinietosum subass. nova.